2001
DOI: 10.1161/01.cir.103.20.2514
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiac Allograft Rejection in Nitric Oxide Synthase-2 −/− and Nitric Oxide Synthase-2 +/+ Mice

Abstract: The data suggest that NO derived from NOS-2 contributes to the inflammatory response and to cardiomyocyte damage and apoptosis during acute cardiac allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 17 publications
4
11
0
Order By: Relevance
“…Since this intervention also decreased iNOS expression, it is possible that decreased nitration resulted secondarily from decreased production of NO, a substrate for peroxynitrite formation. Other studies from the same group using iNOS knockout mice showed decreased apoptosis and lack of nitrotyrosine formation when iNOS Ϫ/Ϫ donor and recipients were used compared with presence of nitrotyrosine when iNOS ϩ/ϩ allografts were used (Szabolcs et al, 2001). These findings are complemented by our studies showing that limitation of NO by two mechanisms, by inhibiting iNOS activity but not expression and decreasing iNOS expression by immunosuppressant therapy, both decreased protein nitration (Pieper et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…Since this intervention also decreased iNOS expression, it is possible that decreased nitration resulted secondarily from decreased production of NO, a substrate for peroxynitrite formation. Other studies from the same group using iNOS knockout mice showed decreased apoptosis and lack of nitrotyrosine formation when iNOS Ϫ/Ϫ donor and recipients were used compared with presence of nitrotyrosine when iNOS ϩ/ϩ allografts were used (Szabolcs et al, 2001). These findings are complemented by our studies showing that limitation of NO by two mechanisms, by inhibiting iNOS activity but not expression and decreasing iNOS expression by immunosuppressant therapy, both decreased protein nitration (Pieper et al, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…This finding agreed with previous studies showing inhibition of nitration using other selective iNOS inhibitors [64,127]. Finally, the role of iNOS in nitrotyrosine formation was firmly established in mouse heart transplants using genetic ablation of iNOS [73].…”
Section: Pathways Of Protein Nitration In Cardiac Rejectionsupporting
confidence: 91%
“…That nitration of cardiac grafts arises specifically from iNOS was clear in studies conducted in iNOS −/− and wild-type mice. Nitrotyrosine was present when either donor or recipient was iNOS positive; however, nitrotyrosine was absent when iNOS −/− donor hearts were transplanted into iNOS −/− recipient mice [73].…”
Section: Cell Localization Of Nitrationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in a rat cardiac allograft model, L-NIL was able to prolong allograft survival from 7 to ϳ10 days under certain conditions (11). Also work with iNOS knockout (iNOS Ϫ/Ϫ involvement of inducible NO formation in rejection was observed (12), whereas in another more recent study where recipients and donor hearts were from iNOS Ϫ/Ϫ mice, participation of iNOS in the inflammatory response leading to rejection was demonstrated (13). Furthermore, participation of iNOS in developing cardiac allograft vasculopathy in the course of chronic rejection has been shown (14).…”
mentioning
confidence: 97%